MIRSDIDIQHAN LUXURY REVIEWS AND ITS HISTORICAL SIGNIFICANCE - Temirov, Sheroz (Educational Research in Universal Sciences, 2023)
The article is devoted to the life and creative heritage of one of the sons of Emir Muzaffar Tsareevich Muhammad Siddiq, who is known in the scientific and literary environment of the emirate under the pseudonym "Hashmat" and "Vohid". He is also a prisoner of the Bukhara Arch under his brother Emir Abdulahad and his heir Emir Alimkhan for 35 years. The authors of the article, based on sources and scientific literature, studied his life, scientific and literary heritage, and also established the composition of his personal library.